An approach to the municipality of Majagua from a tourist perspective - Noa Guerra, Dailén (2026)
Rural tourism activity is conditioned by the characteristics of the region where it operates, which requires broadening the vision of rural tourism beyond its conception as merely a recreational activity offering and service provision. Therefore, a business network must be built or consolidated, tailored to the needs and interests of the rural population. At this point, the local stakeholders involved must establish a coherent relationship among the management of tourist flows, market demand, and the region’s existing reality. The objective of the study is to characterize the municipality of Majagua from a tourism perspective for the gradual incorporation of rural tourism as a factor in local development. A qualitative approach predominates, and the techniques of scientific observation, documentary analysis, and interviews were employed during fieldwork to collect, process, and interpret the available information. The results: the tourism vocation of the municipality of Majagua, in the province of Ciego de Ávila, was confirmed, and a tourism diagnosis was completed. The municipal strategic diagnosis was also updated from a tourism perspective, which favors the development of rural tourism activity, and the need to use rural tourism as a complementary activity was recognized.